Comparative analysis of the leftist ideas of Ali Shariati and Geydar Dzhemal (Journal of Philosophy Culture and Political Science, 2023)
The article provides a comparative analysis of the left-wing religious ideas of representatives of Islamic Marxism: the ideologist of the Iranian Islamic revolution, thinker Ali Shariati and the Islamist Geydar Dzhemal, the owner of the ideas of the Russian-Muslim world and the political integation of the Russian and Muslim worlds. The purpose of the article is to draw attention to the potential danger of politicizing religion, justifying revolution and far-left ideas through religious slogans for a country like Kazakhstan, where there is a huge social inequality and high protest sentiments. Therefore, there is no reason to deny such an opportunity for our country. The January protests of 2022 revealed the catastrophic failure of the state’s social policy. In our context of instability, what ideas will give religious legitimacy to political revolution and pave the way for a political mobilization? The article is based on the conclusion that the extreme ideas that formed the basis of the Islamic revolution in Iran can be attractive not only to the Shiite environment, but also to believers who identify themselves as Sunnis. There is no secret that the ideas of Geydar Dzhemal are popular in the Russian-language information space, who transformed many elements of protest Shiite theology, which served as the religious platform of the revolution, and sought to create a confessionally neutral ideology. Being a member of the mentioned information space, there is a possibility that such ideas will spread in Kazakhstan. Thus, scientific analysis of such thoughts is very important to ensure the stability of the state.Key words: Ali Shariati, Geydar Dzhemal, revolution, Islamic Marxism, Iranian Islamic revolution, Islamic liberation theology, Eurasianism.